2019
DOI: 10.1002/2211-5463.12737
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of roots from resistant and susceptible rice varieties infected with Hirschmanniella mucronata

Abstract: Hirschmanniella mucronata is a plant‐parasitic nematode that is widespread in rice production areas and causes 10–25% yield losses a year on average. Here, we investigated the mechanism of resistance to this nematode by comparing the transcriptomes of roots from resistant (Jiabali) and susceptible (Bawangbian) varieties of rice. Of 39 233 unigenes, 2243. exhibited altered total expression levels between control and infected resistant and susceptible varieties. Significant differences were observed in the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Han et al analysed the early transcriptome of rice in response to infection with Ustilaginoidea virens and found that 16 peroxidase genes were up-regulated in the resistant variety IR28 and down-regulated in the susceptible variety LYP9 [ 45 ]. Similar research was reported for the interaction between rice and Hirschmanniella mucronata [ 46 ], peanut and Puccinia arachidis [ 47 ] , and mulberry and Meloidogyne enterolobii based on transcriptome analyses [ 48 ]. Cytochrome P450 is a supergene family containing haem monooxygenases involved in many metabolic pathways and defence reactions in plants [ 49 ].…”
Section: Discussionsupporting
confidence: 74%
“…Han et al analysed the early transcriptome of rice in response to infection with Ustilaginoidea virens and found that 16 peroxidase genes were up-regulated in the resistant variety IR28 and down-regulated in the susceptible variety LYP9 [ 45 ]. Similar research was reported for the interaction between rice and Hirschmanniella mucronata [ 46 ], peanut and Puccinia arachidis [ 47 ] , and mulberry and Meloidogyne enterolobii based on transcriptome analyses [ 48 ]. Cytochrome P450 is a supergene family containing haem monooxygenases involved in many metabolic pathways and defence reactions in plants [ 49 ].…”
Section: Discussionsupporting
confidence: 74%
“…Two other genes, Os02g0754400 (MR = 95.812) and Os10g0191300 (MR = 81.425) play a role in response to arsenic [83] and silicon [157], respectively (Table 3). However, it was postulated that, Os10g0191300, which encodes a pathogenesis-related protein (Table S10), might be involved in rice defence against insects [158] and fungi [157]. Other pathogen resistance genes are Os03g0760500 (MR = 96.156)-against bacteria [120], and Os10g0335000 (MR = 81.994)-against fungi [159].…”
Section: Co-expression Gene Network Of Os01g0701400mentioning
confidence: 99%
“…Han et al analysed the early transcriptome of rice in response to infection with Ustilaginoidea virens and found that 16 peroxidase genes were upregulated in the resistant variety IR28 and downregulated in the susceptible variety LYP9 [43]. Similar research was reported in the transcriptome of the interaction between rice and Hirschmanniella mucronata [44], peanut and Puccinia arachidis [45], and Mulberry and Meloidogyne enterolobii [46]. Cytochrome P450 is a supergene family containing haem monooxygenases in many metabolic pathways and defence reactions in plants [47].…”
Section: Discussionmentioning
confidence: 79%